2014
DOI: 10.1021/ja505599v
|View full text |Cite
|
Sign up to set email alerts
|

Addition Reaction-Induced Cluster-to-Cluster Transformation: Controlled Self-Assembly of Luminescent Polynuclear Gold(I) μ3-Sulfido Clusters

Abstract: Unprecedented addition reaction-induced gold(I) cluster-to-cluster transformation has been observed in the present work. Reaction of the chlorogold(I) precursor, [vdpp(AuCl)2] (vdpp = vinylidenebis(diphenylphosphine)) containing the diphosphine with unsaturated C═C bond, with H2S resulted in a series of polynuclear gold(I) μ3-sulfido clusters bearing Au(I)···Au(I) interactions; the identities of which have been fully characterized by NMR, electrospray-ionization mass spectrometry, elemental analysis, and singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 86 publications
3
62
0
Order By: Relevance
“…Stokes shift of approximately 138 nm clearly suggest that the luminescence of clusters originates from at riplet parentage, which is assigned to at riplet ligand-to-metal charge transfer ( 3 LMCT) excited state or at riplet ligand-to-metal-metal charge transfer ( 3 LMMCT) excited state. [15] It needs to be stressed that based on the facts of 2.676(2) AuÀAu bond length and the mixed-valence of Au (0/I), the attractive aurophilic interaction should considerably contribute to the PL properties of chiral Au clusters. [16] More intriguingly,these chiral Au cluster assemblies show strong CPL response in the same wavelength region as their PL peak centered at 583 nm (Figure 3c).…”
Section: Zuschriftenmentioning
confidence: 99%
See 1 more Smart Citation
“…Stokes shift of approximately 138 nm clearly suggest that the luminescence of clusters originates from at riplet parentage, which is assigned to at riplet ligand-to-metal charge transfer ( 3 LMCT) excited state or at riplet ligand-to-metal-metal charge transfer ( 3 LMMCT) excited state. [15] It needs to be stressed that based on the facts of 2.676(2) AuÀAu bond length and the mixed-valence of Au (0/I), the attractive aurophilic interaction should considerably contribute to the PL properties of chiral Au clusters. [16] More intriguingly,these chiral Au cluster assemblies show strong CPL response in the same wavelength region as their PL peak centered at 583 nm (Figure 3c).…”
Section: Zuschriftenmentioning
confidence: 99%
“…The dominant PL decay time also follows the order: 50 % n ‐hexane (0.59 μs) <60 % n ‐hexane (0.69 μs) <70 % n ‐hexane (0.79 μs) >80 % n ‐hexane (0.75 μs) >90 % n ‐hexane (0.68 μs) (Figure S7). The microsecond PL decay time and the large Stokes shift of approximately 138 nm clearly suggest that the luminescence of clusters originates from a triplet parentage, which is assigned to a triplet ligand‐to‐metal charge transfer ( 3 LMCT) excited state or a triplet ligand‐to‐metal‐metal charge transfer ( 3 LMMCT) excited state . It needs to be stressed that based on the facts of 2.676(2) Å Au−Au bond length and the mixed‐valence of Au (0/I), the attractive aurophilic interaction should considerably contribute to the PL properties of chiral Au clusters .…”
Section: Figurementioning
confidence: 99%
“…[15] It needs to be stressed that based on the facts of 2.676(2) AuÀAu bond length and the mixed-valence of Au (0/I), the attractive aurophilic interaction should considerably contribute to the PL properties of chiral Au clusters. [15] It needs to be stressed that based on the facts of 2.676(2) AuÀAu bond length and the mixed-valence of Au (0/I), the attractive aurophilic interaction should considerably contribute to the PL properties of chiral Au clusters.…”
Section: Themolecular Formula Of Au 3 [(R)-tol-binap]mentioning
confidence: 99%
“…[13] However, Au···Au interactions have not yet been employed for the construction of organic porous materials. [14] Our group has comprehensively investigated as eries of aryl gold isocyanide complexes with tunable emission properties, polymorphism, and phase transitions. [15] We proposet hat porousc rystals that are formed due to Au···Au interactions between gold isocyanide complexes should exhibit versatile responsive behavior of their emission that depends on the nature of the small guest molecules in their cavities.A fter extensive screenings of gold isocyanide complexes and their crystallization conditions, we found that the bent aryl gold isocyanide complex 1 [16] (Figure 1) forms an extrinsicp orousm aterial due to the manifestation of prominent Au···Au interactions.…”
Section: Introductionmentioning
confidence: 99%